Die noodsaak van kultuurdifferensiasie in die onderwys - Steyn, H. J. (1985)
In this article the author discusses the necessity of cultural differentiation in education. Following a brief introduction in which various viewpoints are compared and contrasted, he outlines the concepts of culture, education and educational system, following this by a discussion of the interaction between culture and the educational system. He further illuminates this by referring to a number of the modes of existence of educational systems. In the physical manifestation of an educational system three main components can be distinguished, viz. educational policy, educational administration and execution of education. After a close reasoning and explication of these points, he comes to the conclusion that the educational system also belongs to culture, in that the educational system is man's most comprehensive cultural product in the field of education and teaching. This leads to the second part of the article where close attention is paid to the links between culture and the aims of education, between culture and the cirriculum. He comes to the final conclusion then that cultural differentiation is essential in education. Each country with a multi-cultural society has to work hard, through research and honest reflection, to enrich and to refine the existing practices in education.